Kegiatan Home Visit dan Pelayanan Kesehatan Korban Banjir di Puskesmas Karang Baru - Fauziah, Fauziah; Desrina, Desrina; Salsabila, Miska; Bengi, Simah; Rahmatika, Nur Azizah; Afriana, Fira Nur (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The floods that hit Aceh Tamiang Regency in 2025 resulted in an increase in cases of infectious diseases, skin disorders, respiratory disorders, and psychological problems such as stress and trauma, especially among vulnerable groups. This activity aims to describe the implementation of integrated health services through home visits and health education for flood victims. The method used was a qualitative descriptive design. The number of patients was 21 people. The activity was carried out on January 7–13, 2026. The results showed that the most common illnesses among disaster victims were coughs (19.05%) and diarrhea (19.05%). In addition, respondents were predominantly female (66.67%) and respondents aged 19-59 years (47.62%) who more frequently underwent health checks in Sukajadi Village, Aceh Tamiang District. It was concluded that the most common illnesses found in disaster victims were coughs and diarrhea. In addition, respondents who more frequently underwent health checks in Sukajadi Village were predominantly female and those aged between 19 and 59 years.